A uniform circular disc of radius R is placed on a frictionless horizontal plane.Another identical disc rotating with angular velocity ω is gently placed on the top of it.The time taken to acquire the final angular velocity can be expressed as b a × μ g R ω Where μ is the coefficient of friction between the plates . What is the value of a + b ?
Liked it? Go here for more
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Frictional torque between two disc with force between them here mg, is given by 3 2 ∗ μ ∗ m g ∗ R 2 − r 2 R 3 − r 3 where R is the outer diameter and r the inner. In our case r = 0.
This is more fundamental. Gud one friend !
Let the final angular velocity be ω ′ . Hence by the conservation of angular momentum we get I ω = ( I + I ) ω ′ or simply ⇒ ω ′ = ω / 2 Now consider a ring of radius x and thickness d x Frictional force on this ring is d F = μ g × ( 2 π x d x π R 2 M ) Where M is the mass of one ring d τ = d F x = R 2 2 μ M g x 2 d x . Total torque, τ = ∫ d τ = R 2 2 μ M g ∫ 0 R x 2 d x or I ( d t − d ω ) = 3 2 μ M g R Negative sign indicates that the angular velocity of the disc decreases with time. Hence d t = 2 μ g M R − 3 I × d ω Solving the integral we get t = 8 3 × μ g R ω
Problem Loading...
Note Loading...
Set Loading...
I post this Same diagram 2nd Time :)
Let mass density of ring is " σ " Consider on the disc an ring element of radius " x " and width " dx " and on this ring consider another circular arc element of width " R d θ " which subtends angle of " d θ " at the centre of ring element. it's mass is " dm " and clearly friction on this element acts tangentially . So we calculate torque on this due to friction and then integrate it !
d m = σ x d θ ( d x ) d f = μ ( d m ) g = σ μ g ( x d x ) d θ .
Now torque due to this is:
d τ = ( d f ) x d τ = σ μ g ( x 2 d x ) d θ ∫ d τ = σ μ g ∫ θ = 0 θ = 2 π d θ ∫ 0 R x 2 d x τ = 3 2 π σ μ g R 3 . . . . . . . . ( 1 ) τ = I α = 2 m R 2 α = 2 σ π R 2 α . . . . . . . ( 2 ) ⇒ α = 3 R 4 μ g . . . . . ( 3 ) .
Using angular momentum conservation of both system about their common centre :
I ω = ( I + I ) ω " ω " = 2 ω . . . . ( 4 ) .
Now using equation of motion ( Since angular accl. is constant )
2 ω = ω − α T ⇒ T = 8 μ g 3 ω R .